Toxoplasmic Encephalitis in an AIDS Patient with Normal CD4 Count: A Case Report - Eissa SOLEYMANI; Farhang BABAMAHMOODI; Lotfollah DAVOODI; Amirkeivan MAROFI; Peyman NOOSHIRVANPOUR (Iranian Journal of Parasitology, 2018)
Toxoplasmic encephalitis is a common presentation of Toxoplasma gondii infection of the central nervous system in the late stage in AIDS patients. A 40 yr old female patient was admitted to Razi Hospital of Qaemshahr City in north of Iran, in Nov 2015, with complaint of headache, blurring of vision, dysarthria and acute left-side hemiplegia and right-side ptosis. Magnetic Resonance Imaging (MRI) was performed with intravenous contrast that showed a ring enhancement lesion in the right basal ganglia showing toxoplasmic encephalitis. Anti-Toxoplasma IgG was positive. HIV antibody test was positive, as well. She was treated successfully with antiparasitic and Anti-HIV drugs and eventually was discharged from hospital. T. gondii infection is commonly detected by serologic tests. Even if in this patient, brain imaging is essential for suitable diagnosis and supervision, its results are not pathognomonic.